Description of the first Brazilian species of the genus Malacocis Gorham (Coleoptera: Ciidae) - Araujo, Lucimar S.; Lopes-Andrade, Cristiano (Zootaxa, 2024)
The genus Malacocis Gorham comprises species characterized by a short and broad body, a pronotum usually narrowed anteriorly, a spinose protibial apex, and a strap-like prosternum with a narrow prosternal process. Currently, it includes two species: the type-species M. championi Gorham, from Guatemala; and M. brevicollis (Casey) from eastern USA and Canada. Here we describe Malacocis pankararu sp. nov. from the Caatinga biome of the Northeast Region of Brazil. The new species is distinguished by its antennae with 10 antennomeres, with the 6th antennomere being wider and more conspicuous than the 5th and 7th. Additionally, males possess two small anterocephalic tubercles, a vertexal sex patch, and a small abdominal sex patch.